Sustaining budget deficits in open economies - Langdana, Farrokh K. (Routledge, 1990)
In both the UK and USA economies the budget deficit remains a central weakness. In the light of this problem this book presents a consistent economic framework for analysing the effects and implications of large bond-financed deficits.